INTEGRATING INDOOR THERMAL COMFORT OPPORTUNITIES FROM TRADITIONAL BUILDING TYPES INTO THE DELIVERY AND MANAGEMENT OF SUSTAINABLE BUILT ENVIRONMENTS - Marcellinus Uwadiegwu OKAFOR (Journal of Construction Project Management and Innovation)
Amid the different contemporary strategies for the delivery and management of sustainable development in the African context, not much emphasis has been placed on seeking for the existence or otherwise, of thermal opportunities from the inherent building types of our forebears. This paper therefore, through case study design approach, reported the developmental trend of indoor thermal comfort opportunities of building types with the design and construction traits representing the historic eras of pre-colonial, colonial and contemporary in Okigwe, Nigeria. The primary data were got from field observations made for 366 days (1 November 2015 – 31 October 2016) on the indoor and outdoor temperature and relative humidity values using Tinytag Explorer 4.9 Germini data loggers and secondary data from the nearest Meteorological Station, Imo State International Cargo Airport, Owerri, Nigeria. The mean annual outdoor temperature and relative humidity values were 29.00C and 69.9% respectively. Analyses of the results using one-way ANOVA test for differences were statistically significant; indoor air temperature [F (2, 1095) = 77.56, p = 0.0001] and relative humidity [F (2, 1095) = 5.76, p = 0.0001]. Further interrogation using the Tukey’s HSD (Honest Significant Difference) post-hoc comparison test amongst the building types revealed that indoor air temperature (27.830C) and relative humidity (71%) of pre-colonial building type were significantly different from those of colonial (28.430C and 67.39%) and contemporary building types (29.270C and 66.75%). The paper recommended that the valid traditional practices as expressed in the pre-colonial building types be re-integrated into the delivery and management of sustainable development in Nigeria. Thus, it concluded that opportunities abound in the indoor thermal comfort traceable to the traditional building (pre-colonial) types of our forebears as they performed thermally better than colonial and contemporary building types.